2007
DOI: 10.1108/02621710710726071
|View full text |Cite
|
Sign up to set email alerts
|

Chairman of the board: demographics effects on role pursuit

Abstract: Purpose -This paper aims to undertake a study of national configurational demographics in order to determine the spread of understanding of the chairman's role, performance and contribution. Design/methodology/approach -Qualitative methodology, exploratory in nature through in-depth interviews and workshop discussion involving 103 UK, US and Australian participants, was undertaken. Findings -The role of chairman is considered as having a distinct effect on board dynamics, role and contribution and the monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 45 publications
0
35
1
Order By: Relevance
“…Chair of the board (COB) is regarded as "minder of the CEO" and "mentoring of the CEO and executive management" (Kakabadse & Kakabadse, 2007). Role separation of CEO from COB influences the effectiveness of the board and the firm.…”
Section: Chair/ceo Dualitymentioning
confidence: 99%
“…Chair of the board (COB) is regarded as "minder of the CEO" and "mentoring of the CEO and executive management" (Kakabadse & Kakabadse, 2007). Role separation of CEO from COB influences the effectiveness of the board and the firm.…”
Section: Chair/ceo Dualitymentioning
confidence: 99%
“…Scholars have observed that chairmen of boards perform their role(s) in a wide variety of ways in different board models (Kakabadse and Kakabadse 2007a;Stewart 1991). However, all board chairmen are responsible for: (i) the conduct and composition of the board (ii) determining the agenda of board meetings (iii) appointing and dismissing the CEO (iv) chairing the annual general meeting of shareholders and (v) ensuring that all board members have the necessary information to perform their job (Hill 1995;McNulty and Pettigrew 1999;Roberts and Stiles 1999).…”
Section: The Dutch Corporate Governance Systemmentioning
confidence: 99%
“…However, all board chairmen are responsible for: (i) the conduct and composition of the board (ii) determining the agenda of board meetings (iii) appointing and dismissing the CEO (iv) chairing the annual general meeting of shareholders and (v) ensuring that all board members have the necessary information to perform their job (Hill 1995;McNulty and Pettigrew 1999;Roberts and Stiles 1999). Furthermore, the chairman's responsibility to maintain a healthy bilateral dialogue with managing directors is often posited as critical to the effectiveness of boards of directors and their contribution to a firm's long-term survival (Kakabadse and Kakabadse 2007a).…”
Section: The Dutch Corporate Governance Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diversity of gender, age and race; percentage of executive v. non-executive members; chair/CEO duality; board size; number of meetings; information availability; and board member equity ownership (e.g., Jensen, 1993;Milliken and Martins, 1996). Furthermore, research in the UK and the Commonwealth countries -where the roles of the chair and the CEO are usually separated -has revealed more about the individual impact of the chair and the CEO on board effectiveness (Cadbury, 1992;Pettigrew and McNulty, 1998;Leblanc, 2004;Dahl, 2005;Kakabadse and Kakabadse, 2007).…”
Section: Better Self-management By the Boardmentioning
confidence: 99%